Respuesta :

Answer:  a^3 + 3a^2b + 3ab^2 + b^3

========================================================

Explanation:

Cubing something means we're multiplying it by itself three times

Something like m^3 means m*m*m

So (a+b)^3 means (a+b)*(a+b)*(a+b)

Let's focus on (a+b)*(a+b) for now. We would use the FOIL rule to find that

(a+b)*(a+b) = a^2 + 2ab + b^2

So we can say

(a+b)*(a+b)*(a+b) = (a+b)(a^2 + 2ab + b^2)

-------------------------

Now let

c = a+b

that way we then have,

(a+b)(a^2 + 2ab + b^2) = c(a^2 + 2ab + b^2)

From here, distribute that 'c' through to each term

c(a^2 + 2ab + b^2)

a^2*c + 2abc + b^2*c

a^2( c ) + 2ab( c ) + b^2( c )

Next, replace c with a+b and apply distribution three more times

a^2( c ) + 2ab( c ) + b^2( c )

a^2( a+b ) + 2ab( a+b ) + b^2( a+b )

a^3 + a^2b + 2a^2b + 2ab^2 + ab^2 + b^3

a^3 + 3a^2b + 3ab^2 + b^3

You could also apply the Binomial Theorem to get the same result. The binomial coefficients can be computed through the combination formula, or through using Pascal's Triangle.

ACCESS MORE